Studi In Silico Sekuen NONEXPRESSOR OF PATHOGENESIS-RELATED GENES 1 (NPR1) pada Jeruk yang Terkait dengan Resistensi Huanglongbing - Kristianto Nugroho; Tri Joko Santoso; Mia Kosmiatin; Dewi Sukma; Agus Purwito (Innovation Centre for Tropical Sciences, 2025)
The evaluation of citrus resistance to Huanglongbing (HLB) disease is still challenging due to the incapability of the bacteria to be cultured purely in artificial medium, the complexity of inoculation methods, and the long duration required for phenotypic observation. Thus, the use of molecular markers is one of the alternatives to solve this problem. The focuses of this study were to perform in silico analysis of the nucleotide variations in NONEXPRESSOR OF PATHOGENESIS-RELATED GENES 1 (NPR1) gene sequence among several citrus genotypes whose resistance information to HLB have been known previously and to employ phylogenetic analysis among them. The NPR1 gene sequences from 20 genotypes which consisted of 14 citrus and six relative genotypes were collected in silico from Citrus Genome Database and analyzed using multiple sequence alignment program. A total of six interesting SNPs that could distinguish between susceptible and resistant citrus genotypes were detected in this study. As many as five SNPs were non-synonymous, while only one synonymous SNP that did not cause the amino acid change was identified in this study. The phylogenetic analysis also revealed the separation between susceptible and tolerant/resistant citrus genotypes in two main clusters. The SNPs found in this study are expected to be useful for designing new functional markers as a selection tool in future studies. Keywords: in silico, molecular marker, phylogenetic analysis, selection tool, SNP